PROBLEMS IN LEARNING “TELAAH TEKS INGGRIS IQT” IN THE ILMU AL-QUR’AN AND TAFSIR CLASS - Nurhayati, Sri (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This study is trying to convey, describe and look for the solution on the students of Ilmu al-Qur’an and Tafsir problems on the “Telaah Teks Inggris IQT” class. This study was conducted in STAIN Pamekasan with respondents from students of Ilmu al_Qur’an and Tafsir. This study is a descriptive qualitative research. The data is taken through observation, interview and documentation. The result of this research show that the students’ background knowledge, either their knowledge on Islamic education or English, influence the process of interpreting the English text. These differences also influence their motivation in learning English. Another factor affecting the students’ competence is the hoterogenousity of the students’ characteristics which often lead to problems. After identifying all problems faced by the students of Ilmu al-Qur’an and Tafsir, the lecturer can formulate the best technique in teaching English especially for Telaah Teks Inggris class where English is their second/ foreign language.